THE INFLUENCE OF JOB TRAINING AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF WORK PRODUCTIVITY AND THE MODERATING ROLE OF WORKLOAD AT PT. DATA LINK GROUP (International Journal of Scientific Research and Management (IJSRM), 2025)
The purpose of this study is to examine the influence of job training and work environment on employee performance: the mediating role of work productivity and the moderating role of workload at PT. Data Link Group. This research adopts an individual-level analysis, with the population and sample comprising 130 employees of PT Data Link Group. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results reveal that job training, work environment, work productivity, and employee performance at PT Data Link Group are generally well-implemented. Job training has a positive and significant effect on employee performance. Similarly, the work environment also demonstrates a positive and significant effect on employee performance. Moreover, job training and work environment significantly enhance employee productivity. In turn, work productivity has a positive and significant influence on employee performance. The findings further indicate that job training significantly affects employee performance through the mediation of work productivity. However, workload does not significantly moderate the relationship between work productivity and employee performance.